Synthesis of mono- and dinuclear vanadium complexes and their reactivity toward dehydroperoxidation of alkyl hydroperoxides - Schmidt, Anna-Corina; Hermsen, Marko; Rominger, Frank; Trapp, Oliver; Schaub, Thomas (Inorganic chemistry, 2017)
Several vanadium(V) complexes with either dipic-based or Schiff base ligands were synthesized. The complexes were fully characterized by elemental analysis, IR, 1H, 13C, and 51V NMR spectroscopy, as well as mass spectrometry and X-ray diffraction. Furthermore, they were tested toward their catalytic deperoxidation behavior and a significant difference between 4-heptyl hydroperoxide and cyclohexyl hydroperoxide was observed. In the case of 4-heptyl hydroperoxide, the selectivity toward the corresponding ketone was higher than with cyclohexyl hydroperoxide. DFT calculations performed on the vanadium complex showed that selective decomposition of secondary hydroperoxides with vanadium(V) to yield the corresponding ketone and water is indeed energetically feasible. The computed catalytic path, involving cleavage of the O-O bond, hydrogen transfer, release of ketone/water, and finally addition of hydroperoxide, can proceed without the generation of radical species.
Gesehen am 18.05.2018